2001
DOI: 10.2514/2.5719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sides-Spillage from Airframe on Scramjet Engine Performance

Abstract: Pre-compression by the windward surface of the aerospace plane is necessary for scramjet operation. However, this pre-compression causes spillage from the high-pressure windward surface toward the sides of the plane. In order to examine the effects of this side-spillage, the performance of a scramjet engine was evaluated using a 1-D flow model, and payload to the low earth orbit estimated using an aerospace plane flight simulation. Prior to the simulation, tests with scramjet inlet models were conducted in a M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Provision of fences or walls in the sides of a nonaxisymmetric intake is suggested and used by many researchers 15,16 to reduce the amount of side spillage. In the present case also a side fence is provided stretching from the nose of the intake to the engine cowl lip.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Provision of fences or walls in the sides of a nonaxisymmetric intake is suggested and used by many researchers 15,16 to reduce the amount of side spillage. In the present case also a side fence is provided stretching from the nose of the intake to the engine cowl lip.…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies are carried out by considering two-dimensional (2D) domains without addressing the issue of side spillage. Only a few studies [13][14][15][16] are carried out to analyse the phenomenon of side spillage. A combined experimental and CFD study carried out by Nguyen et al 13 has shown a less than 4% difference for mass capture ratios predicted by CFD and those obtained experimentally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mrozinski and Hayes examined a variablegeometry inlet design consisting of a cowl and a sidewall with a gap in the cowl-sidewall interface [2]. Tani et al [3] conducted their experiments in a Mach 4 wind tunnel to investigate the effect of inclination of airflow due to side spillage on inlet performance with the variable geometry inlet model, achieved by exchangeable ramp blocks. Bedarev et al [4] studied a geometry variation, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The air entering the engine passed a planar shock wave generated by the forebody, which was calculated with the 2D oblique shock wave relations. The end effect at both sides of the forebody 16) was neglected for the sake of simplicity. In the calculation of the engine performance, the angle of attack, i.e., the angle between the free-stream direction and airframe axis, was fixed to be 3 degrees.…”
Section: (A) Scramjet Engine Performancementioning
confidence: 99%